Sound absorption behavior of repurposed waste fibers: Effects of fiber size, density, and binder concentration. (January 2023) - Gomez, Tomas Simon; Zuluaga, Santiago; Jimenez, Maritza; de la Prida, Daniel; Pedrero, Antonio; Navacerrada, María Ángeles; Restrepo-Osorio, Adriana; Fernandez-Morales, Patricia
Highlights: The study and development of natural fiber-based materials for acoustic applications aim to contribute to sustainable development goals. An Analysis of variance (ANOVA) proved that density and fiber size had a significant effect on the sound absorption coefficient. Denim fibers showed a smaller diameter, which indicates a better sound absorbing performance. Denim nonwovens presented a sound absorption comparable to glass fiber-based materials. Binder content did not show a significant effect on sound absorption in the concentrations applied in this research. Abstract: The following research presents the development of natural fiber-based nonwovens as a potential substitute for acoustic materials commonly made of synthetic and mineral fibers and an analysis of variance (ANOVA) which deals with the effect of fiber size, density, and binder content in the sound absorption coefficient of such materials. The characterization of the fibers showed the potential of denim fibers, which could easily outperform fique and coir, which was later confirmed in the acoustic tests. The analysis of variance showed that density and fiber size had a significant effect on the sound absorption coefficient. Denim nonwovens presented a sound absorption comparable to glass fiber-based materials, thus, demonstrating the technical potential of natural fibers to replace traditional materials.